INFLUENCE OF TRAINING ON PUBLIC PARTICIPATION IN COUNTY GOVERNANCE IN NAROK COUNTY, KENYA - James Oloisiriri Ngeeti; Dr. Elijah Odhiambo (IJRDO - Journal of Social Science and Humanities Research, 2020)
The conversion of the amended constitution (2010) in Kenya opened room for citizen participation by embedding participatory government as a principal of governance which binds government stakeholders; unfortunately there is improper public involvement in policy process in Narok County. Over years, Kenya has little by little shifted from federal to a decentralized or a democratic form of governance; The 47 counties in Kenya are gradually moving to such form of governance by considering public participation, while a county like Narok is not properly conducting a successful public participation for its governance. Regardless of devolution in Kenya which embraces participatory government, county government of Narok has not been properly focusing or considering it. The residents of Narok County complain of lack of consideration of their views when the county government is making any bill and when conducting a specific project. The rationale of the survey was to focus factors affecting citizen participations in county governance in Narok County. A descriptive research survey was use. A descriptive research survey was used. A population of 10,342 households was targeted. A sample size of 400 was considered using Miller and Brewer (2003) formula. A snowball sample procedure was used. The collection of data was by the use questionnaires and interview schedules tools. A pilot study was conducted in Transmara West Sub-County for the purpose of testing the instrument’s validity and also reliability of the instrument. Data was analyze descriptively using SPSS and presented in percentages, frequencies and tables. The outcome of the study help county officials, administrators, law makers and even citizen in conducting a successful public participation for smooth development. From the results a higher percentage of the respondents of about 62% indicated that there was lack of coordination and communication from the county administrators for public participation. A percentage of 82% and 70% of respondent responded that there was lack of public training and poor governance respectively while. The research established that social and economic factors, training and governance influence public participation. This project recommends that the county management team and administrators should ensure that there is training and sensitization of public members, allocation of funds and practice of good governance which embraces equality, participation, democracy, transparency, accountability and efficiency.